Panel discussion discus - Prendergast, K. (Modern Athlete & Coach, 2014)
An interview with Australian coaches, including Grahame Pitt, Merv Kemp, and Ken Harradine is presented. When asked about the stagnation, and deterioration in the level of performance in discus throw between men and women divisions, they refer on the standards of the athletes. They mention that their is a lack of progress in the women division in Australia. Ken believes that there is a high standard coaches in Europe equated to Australia